Difference of Children Ages 5-6 Years of Independence Viewed from The Caregiver (Parents and Grandparents) in Kindergarten Kartini 1 and Kartini 2 - Rahmawati, Enni; Diana, Diana (BELIA: Early Childhood Education Papers, 2016)
The childâs independence is characters that make a child inÂ  aged 0-6 years can stand by theirselves without depending in others, especially their parents. While many parents are working, parenting will in the hand of close relatives i.e. Grandma/Grandpa. This research aims to find out if there is a difference ofÂ  childâs independence in terms ofÂ  the subject matter ofÂ  parenting (parents and grandparent). The population ofÂ  this research are all students in kindergartenÂ  Kartini 1, andÂ  Kartini 2. The techniques that use in this research is purposive sampling technique. This research using a sample ofÂ  children in the range ofÂ  aged 5-6 years in class B that is parentingÂ  by parents and grandparent with a total number ofÂ  30 students. The Method analysis data collection is using childâs independence scale . Methods analysis data in this research using program SPSS16. This is demonstrated by the acquisition of the value t calculate < t table (0,268 < 2,048)and the value ofÂ  sig. > 0.05 (0,791 > 0.05), then Ho denied. The conclusions ofÂ  this research showed that there are differences between childâs independence that was parenting by their parents and grandparent.